Implementasi Tata Kelola Organisasi: Manfaat Sistem Informasi Akuntansi Berbasis Web [Implementation of Organizational Governance: The Benefits of Web-Based Accounting Information Systems] - Agustina, Heni; Elfita, Rizki Amalia; Wulan, Tri Deviasari; Arifianti, Novalina (Indonesia Berdaya, 2025)
Abstract. Organizational governance is one of the ways in which an organization structures and organizes its groups or activities. Good organizational governance can be achieved by utilizing an accounting information system. A website-based accounting information system is a system that can provide benefits such as transparency, efficiency, accountability, and ease of reporting and auditing. Accounting and financial reporting at the Maahad Tahfiz Al-Quran Darul Falah Selangor Malaysia Islamic boarding school currently still uses manual financial reporting using books. Therefore, the community service team offered to assist in managing the organization using a web-based accounting information system. The web-based accounting information system is expected to help the Islamic boarding school manage its organization transparently, quickly, and efficiently. The results of this community service initiative show that the boarding school administrators are now able to operate the accounting information system independently after undergoing training and have been able to apply better organizational management principles. Overall, this community service activity has had a positive impact in strengthening the organization, improving operational efficiency, and promoting the use of technology to support the sustainability of the boarding school. Abstrak. Tata Kelola organisasi merupakan salah satu bentuk usaha organisasi dalam Menyusun dan mengorganisasikan kelompok atau usahanya. Dalam mencapai tata Kelola organisasi yang baik dapat terwujud dengan memanfaatkan sistem informasi akuntansi. Sistem informasi akuntansi berbasis website merupakan sistem yang dapat memberikan manfaat seperti transparansi, efisiensi, akuntabilitas, serta kemudahan dalam pelaporan dan audit. Pelaporan akuntansi dan keuangan di Pondok Pesantren Maahad Tahfiz Al-Quran Darul Falah Selangor Malaysia saat ini tata Kelola pondok pesantren masih menggunakan pencatatan laporan keuangan secara manual menggunakan buku.  Oleh karena itu tim pengabdian Masyarakat menawarkan untuk membantu mengelola organisasi berbasis sistem informasi akuntansi berbasis web. Sistem informasi akuntansi berbasis web diharapkan dapat membantu pondok pesantren dalam mengelola organisasi secara transparan cepat dan efisien. Hasil dari pengabdian Masyarakat ini menunjukkan bahwa pengelola pondok pesantren mampu mengoperasikan SIA secara mandiri setelah dilaksanakannya pelatihan, dan sudah mampu menerapkan prinsip tata Kelola organisasi lebih baik. Secara keseluruhan, kegiatan pengabdian masyarakat ini mampu memberikan dampak positif dalam memperkuat organsisasi, meningkatkan efisiensi operasional, serta mendorong pemanfaatan teknologi dalam mendukung keberlanjutan pondok pesantren.